The doctrine of "Reasonable Doctor" in medical negligence: Need to be more reasonable. (November 2022) - Naik, B. Sadananda; Basu, Adhish
Abstract: The model of a 'reasonable doctor' has been quite successfully used to deliver justice in disputes involving medical negligence. However, many a times a doctor is held guilty of negligence when viewed through the narrow lens of an ideal 'reasonable doctor' and without looking into the circumstances under which he was working which could have actually led to the alleged act of negligence. This short write-up highlights the importance of applying this doctrine more reasonably in the best interest of all stake holders and the drawbacks of the doctrine of 'reasonable doctor' in adjudicating medical negligence cases with few international case laws.